2014
DOI: 10.5755/j01.ms.20.2.6311
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Transport and Magnetoresistance in Single-Wall Carbon Nanotubes Films

Abstract: Electrical transport properties and magnetoresistance of single-wall carbon nanotubes (SWCNT) films were investigated within temperature range (2-300) K and in magnetic fields up to 8 T. A crossover between metallic (dR/dT > 0) and non-metallic (dR/dT < 0) temperature dependence of the resistance as well as low-temperature saturation of the resistance in high bias regime indicated on the diminishing of role of the contact barriers between individual nanotubes essential for the charge transport in SWCNT arrays.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 15 publications
1
1
0
Order By: Relevance
“…As one can see in Fig. 2, this dependence describes well the experimental results with the characteristic field E 0 values equal to 5.8⋅10 5 , 5.2⋅10 5 , and 1.4⋅10 6 V/cm for the samples S1, S2 and S3, respectively. Using the obtained values of E 0 and T 0 , one can calculate the localization length of charge carriers:…”
Section: Resultssupporting
confidence: 84%
See 1 more Smart Citation
“…As one can see in Fig. 2, this dependence describes well the experimental results with the characteristic field E 0 values equal to 5.8⋅10 5 , 5.2⋅10 5 , and 1.4⋅10 6 V/cm for the samples S1, S2 and S3, respectively. Using the obtained values of E 0 and T 0 , one can calculate the localization length of charge carriers:…”
Section: Resultssupporting
confidence: 84%
“…These studies have been carried out using various types of CNT arrays (carbon nanotubes bundles, aligned fibers, networks, films, mats, etc. ), and there was found that the electrical properties strongly depend on morphology of arrays and the quality of contacts between individual nanotubes (see, for example [3][4][5][6][7]). In fact, since CNT arrays are formed by randomly distributed nanotubes, the contacts play the role of insulating barriers along the conduction path.…”
Section: Introductionmentioning
confidence: 99%